2012
DOI: 10.1158/1940-6207.capr-11-0427
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Protein Pathway Activation Mapping of the Progression of Normal Skin to Squamous Cell Carcinoma

Abstract: Reverse phase protein microarray analysis was used to identify cell signaling derangements in squamous cell carcinoma (SCC) compared with actinic keratosis (AK) and upper inner arm (UIA). We analyzed two independent tissue sets with isolation and enrichment of epithelial cells by laser capture microdissection. Set 1 served as a pilot and a means to identify protein pathway activation alterations that could be further validated in a second independent set. Set 1 was comprised of 4 AK, 13 SCC, and 20 UIA. Set 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 40 publications
3
89
0
Order By: Relevance
“…Furthermore, UVB-induces phosphorylation of 4EBP1, S6K, and AKT, suggesting an important role of the mTOR pathway in tumor initiation and progression (47). In our studies, pretreatment with C3 complex and FGFR inhibitor attenuated UVB-induced mTORC1 and mTORC2 activation.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, UVB-induces phosphorylation of 4EBP1, S6K, and AKT, suggesting an important role of the mTOR pathway in tumor initiation and progression (47). In our studies, pretreatment with C3 complex and FGFR inhibitor attenuated UVB-induced mTORC1 and mTORC2 activation.…”
Section: Discussionsupporting
confidence: 56%
“…Squamous cell carcinomas typically have hyperactive EGFR/ERK and PI3K/AKT/mTOR signaling pathways. [26][27][28]31 One consequence of activation of these pathways is phosphorylation of the ribosomal protein S6. S6 is a component of the 40S ribosomal subunit and is thought to have a role in modulating efficiency of mRNA translation initiation.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Squamous cell carcinomas of the interfollicular epidermis, oral cavity, oropharynx, and lung very frequently have gene mutations and amplifications that hyperactivate their EGFR/ERK signaling pathway. [26][27][28] Our recent study identified EGFR/ERK signal pathway hyperactivation as necessary and sufficient to drive laminin g 2 overexpression in cultured human premalignant epithelial and squamous cell carcinoma cell lines and also found that the HPV16 E6 oncoprotein also induces laminin g 2 overexpression. 29 Laminin g 2 overexpression proved to require the ERK-activated RSK kinase and to correlate with increased phosphorylation of the translation factor eIF4B at S442 and of ribosomal protein S6 at S235/236.…”
mentioning
confidence: 96%
“…Spearman's Rho correlations were also taken into consideration for each experimental set, with experimental sets ultimately being compared with each other to isolate endpoints unique to adipogenesis. Alterations in signaling for inhibitor treated experimental sets were further examined using CScape pathway maps to reflect signaling pathway changes relative to the related untreated samples (25). These maps examined alterations in the early and late signaling events by analysis of day 4 and day 8 data.…”
Section: Methodsmentioning
confidence: 99%